MAGERSARI ATAS TANAH KARATON KASUNANAN SURAKARTA DI PENGGING (DESA BENDAN KABUPATEN BOYOLALI) - , NUGROHO SHIDIQ SANTOSO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research on Land lodger area in Surakarta palace compound in Pengging (Village Bendan) Boyolali specifically discuss existing tenant Pengging (Village Bendan) Boyolali, and legal issues arising from the tenant as well as how to deal with the legal issues. Type of research is included in this type of empirical legal research or sociological research is a way to solve a problem by first examining existing secondary data and then proceed with the field research in the to obtain primary data. This research takes a subject that includes respondents are citizens Pengging (Village Bendan) Boyolali the tenant and the officials did Surakarta palace compound and various official sources, namely Boyolali Land Office, The Village Bendan (Pengging), local PPAT. Means of collecting data in this study are list of questions used to guide the interviews conducted with the question and answer directly to the respondents and resource person. The data have been obtained analysed qualitatively. The results of Lodger Land Surakarta palace compound in Pengging (Village Bendan) Boyolali namely: 1) In Pengging (Village Bendan) people who do tenant of land formerly the Palace of Surakarta because Pengging (Village Bendan) is part of the Royal Palaces of Surakarta that live by the servant in palace of the Palace of Surakarta, 2) The tenant in Pengging (Bendan village) there are some legal issues, namely: the Surakarta palace compound has no clear data on existing land Pengging SG (Village Bendan)